2013
DOI: 10.2337/dc12-0948
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Personalized Artificial Pancreas

Abstract: OBJECTIVEAn artificial pancreas (AP) that automatically regulates blood glucose would greatly improve the lives of individuals with diabetes. Such a device would prevent hypo- and hyperglycemia along with associated long- and short-term complications as well as ease some of the day-to-day burden of frequent blood glucose measurements and insulin administration.RESEARCH DESIGN AND METHODSWe conducted a pilot clinical trial evaluating an individualized, fully automated AP using commercial devices. Two trials (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 27 publications
2
77
0
Order By: Relevance
“…The AP system architecture has been clinically evaluated for three potential configurations, based on the hardware platform where the controller was implemented, specifically: computer/laptop [7,[16][17][18], tablet [8,19,20] and smartphone [21]. In this study, we examine two possible AP hardware configurations; we refer to them as Configuration A and Configuration B.…”
Section: Hardware Configurations Of the Ap Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The AP system architecture has been clinically evaluated for three potential configurations, based on the hardware platform where the controller was implemented, specifically: computer/laptop [7,[16][17][18], tablet [8,19,20] and smartphone [21]. In this study, we examine two possible AP hardware configurations; we refer to them as Configuration A and Configuration B.…”
Section: Hardware Configurations Of the Ap Systemmentioning
confidence: 99%
“…Hence, mp-MPC is regarded as a potential alternative for low-power hardware implementations [75,76]. The idea of an explicit MPC-based AP system has been proposed in [16,77,78] with simplified computational models.…”
Section: Explicit/multi-parametric Mpcmentioning
confidence: 99%
“…We hypothesized that our algorithm proposing a microbolus every 5 min, mimicking the physiological pulsatile insulin secretion, 27,28 could contribute to insulin action optimization and favor stability. This pulsatile administration is different than the strategy used in other CL studies, [7][8][9]13,15,29 in which a change in the insulin delivery rate is made so insulin is distributed throughout the actuation period.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Meanwhile, improvements of MPC algorithms incorporating safety components (insulin on board constraint) led, in a short term pilot evaluation, to overcoming small unannounced meals without postprandial hypoglycemia. 18 In a pilot experiment, another team showed that the regulation of blood glucose was feasible in a closed-loop system without any meal announcement. 19 Another team reported that their MPC controller was at least as effective as conventional therapy in managing rises in blood glucose following breakfast.…”
Section: Discussionmentioning
confidence: 99%